2010 IEEE International Ultrasonics Symposium 2010
DOI: 10.1109/ultsym.2010.5935434
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of chirp coded excitation in ultrasound superharmonic imaging

Abstract: Abstract-Superharmonic imaging (SHI) provides improved spatial resolution and contrast detection with low reverberation artifacts by combining the third, fourth and fifth harmonics of the nonlinear received signal. The aim of this study is to increase the signal-to-noise ratio (SNR) with improved axial resolution and reduced ripple artifacts in the SHI using chirp coded excitation. Experiments are performed using a 2.25 MHz transducer mounted coaxially at a distance of 1-10 cm with a 0.2 mm hydrophone in a tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Several recent studies have used chirps for superharmonic imaging and achieved results similar to those presented in this section [24]- [26].…”
Section: A Without Filtering In the Fcht Domainsupporting
confidence: 58%
See 1 more Smart Citation
“…Several recent studies have used chirps for superharmonic imaging and achieved results similar to those presented in this section [24]- [26].…”
Section: A Without Filtering In the Fcht Domainsupporting
confidence: 58%
“…To improve the SNR and penetration depth, chirp coded excitation techniques have been used for tissue harmonic imaging instead of conventional pulsed excitation [21]- [23]. Chirp excitation has already been employed for superharmonic imaging by [24]- [26]; however their results showed that linear frequency modulated (LFM) signals underperformed due to the high sidelobe levels caused by the spectral overlap between the harmonic components.…”
Section: Introductionmentioning
confidence: 99%